Adaptive Thresholding of CNN Features for Maize Leaf Disease Classification and Severity Estimation - Harry Dzingai Mafukidze; Godliver Owomugisha; Daniel Otim; Action Nechibvute; Cloud Nyamhere; Felix Mazunga (MDPI, 2023)
Abstract